Integrating stereo-elastic packing into ecological floating bed for enhanced denitrification in landscape water. (March 2020) - Song, Jia; Li, Qian; Dzakpasu, Mawuli; Wang, Xiaochang C.; Chang, Nini
Graphical abstract: Highlights: Enhancement of N removal in EFBs by the stereo-elastic packing biomass carriers. Stereo-elastic packing intensify denitrification rates on ceramisite and plant roots. Stereo-elastic packing inhibit slightly plant growth but increase sediment accretion. Enrichment of denitrifying bacteria on carriers supports intensified denitrification. Abstract: The effects of stereo-elastic packing, as additional bio-carriers, on nitrogen removal in enhanced ecological floating beds (EFBs) are evaluated. Enhanced EFBs with additional stereo-elastic packing was demonstrated to enhance maximum TN removal efficiency (65.8%) over that of EFBs with plant and ceramisite only (54.9%). Performance enhancement was attributable to a 40.6% increase in sediment N accretion and intensification of denitrification by biomass on other carriers in the presence of stereo-elastic packing. Nonetheless, nitrogen uptake by plants was inhibited slightly. Stereo-elastic packing intensified denitrification rates on plant roots and ceramisite by increasing the attached biomass and enhancing the biomass activity, albeit to different extents. The increase in denitrification rate on plant root by 25.7% was significantly higher than that of 4.6% on ceramisite via increased NO2 -N removal. Moreover, bacterial diversity on the carriers was significantly altered, and the enrichment of genera such as Aridibacter, Hyphomicrobium and Gemmobacter promoted denitrification processes.